PADANAN ISTILAH HUKUM ARAB-INDONESIA BERITA DARING ALJAZEERA - Nining, Nining Yuningsih; Abdullah Maulani; Waqi Ats-Tsaqofi; Ahmad Hifni; Darsita Suparno; Fathalah Mohamed Fathalah (Epigram, 2024)
This study aims to analyze the vocabulary of law terms published on the online news site Al Jazeera in 2012-2024 and translated from Arabic into Indonesian using free translation. The method used in this study is a qualitative-descriptive method by conducting a significant and comprehensive search based on the analysis of certain data. This study collects and analyzes the vocabulary of law terms. The data sources used are primary sources from online news site Al Jazeera in 2017-2024. The secondary sources are several dictionaries such as the Arabic Akbar Dictionary by Al-Mujtahid, A. Ṭaha Ḥusayn al-Mujȃhid and A.Atho'illah Fatani al-Khalîl, the Al Munawwir Dictionary (Arabic-Indonesian and Indonesian-Arabic) by Ahmad Warson Munawwir, the Law Dictionary by Harith Suleiman Faruqi, The Contemporary English-Indonesian Dictionary by Peter Salim, Dictionary of Popular Legal Terms by Jonaedi Efendi, Ismu Gunadi Widodo and Fifit Fitri Lutfianingsih, Great Dictionary of Indonesian Language (KBBI Online), Al-Ma'ani Online Dictionary, google translate, and the internet as support.